The use of code-switching on Twitter among Malaysian teenagers / Tengku Mohamad Faiz Tg Azhar - Tengku Mohamad Faiz, Tg Azhar (2019)
It is common for Malaysians to be bilingual or multilingual. Therefore, code-switching is a common phenomenon to occur in a conversation. This study was conducted in order to determine the types of code-switching and its language functions used in Twitter. This study was based on the tweets made by secondary school students from a boarding school in Malaysia. The types and the primary functions of the tweets were identified following Poplack’s (1980) types of code-switching and Appel and Muysken’s (2005) functions of code-switching. The findings showed that the majority of the code-switch occurrences were done intra-sententially. Besides, for both perceived and intended language functions, referential function is the most common among the participants. This study showed how language and code-switching were used in the social media. Besides, the present study also provided insights on which type of code-switching and their language functions so that proper measures could be taken. The findings of this study are not applicable to the general population as the number of the participants are limited. Due to time constraint, the interviews with the participants could not be carried out.